Analisis Indeks Kebutuhan Lahan dan Biaya dari Perencanaan IPAL Terpadu di Kawasan Aerocity X - Adryan Lukman Indira; Didin Agustian Permadi; Etih Hartati (Fakultas Teknik, 2021)
District Aerocity X in Kabupaten Majalengka is a commercial and industrial area that enhances economic growth in Provinsi Jawa Barat. The district with an area of 3,480 ha is integrated into the domestic sector. However, this area also has the potential to cause harm if the waste is not treated. Following PP No 142 Tahun 2015, each industrial area must provide an effective and efficient wastewater treatment plant (WWTP). This design plan begins with the analysis of issues on the study site . The data were obtained using the Aerocity X District Pre-Development Office study method . The method of designing effective alternatives for WWTP used the weighted ranking technique (WRT), each alternative was compared with two fundamental, technical and non-technical aspects. The purpose of this design plan is to analyze the index of land and cost requirements for WWTP. The yield of wastewater was 3.99 m3/s. The most effective land and the cost is complete mix-activated sludge. The result of installing the design plan requires an area of 9,446.5 m2/m3 of wastewater and a cost of Rp5,619.53x106/m3 of wastewater.